Implementasi PSAK No.14 Pada Aplikasi Inventory Skuy Store Berbasis Web - Yuda, Marsa Prayuda; Dery Sofya, Nora (Management of Information System Journal, 2023)
This research aims to implement PSAK No. 14 in the web-based inventory application for Skuy Store. Skuy Store is a shop located in Semamung Village, Sumbawa Regency, that sells various types of products. The problem faced is the use of physical notebooks for transaction recording, which is prone to damage and loss, resulting in disorganized stock management. This study utilizes qualitative data collection methods such as observation, interviews, documentation, and literature review. The development method employed is the waterfall method using Hypertext Preprocessor (PHP) language and the CodeIgniter Framework. The Skuy Store application is built with three types of users: admin, cashier, and owner, each having different access rights. The admin has full access to manage inventory, sales, purchases, accounting, and financial reports. The cashier has limited access to handle sales and purchases, while the owner has restricted access to view financial reports. With this application, it is expected that the management of inventory, sales, purchases, and financial data can be better controlled, reducing financial losses, and improving the efficiency of stock management. The result of this research is the implementation of the Skuy Store inventory application that complies with PSAK No. 14. This application assists in the management of inventory, sales, purchases, and financial reports more effectively and efficiently. Users can easily record transactions, manage stock, and view real-time financial reports. With this application, it is expected that Skuy Store can enhance inventory control and financial performance